2020
DOI: 10.4103/ijem.ijem_627_19
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile hypothyroidism: A clinical perspective from Eastern India

Abstract: Introduction: Juvenile hypothyroidism (JH) can have deleterious effects on growth, pubertal development, and scholastic performance of children. In India, there is a paucity of data on acquired hypothyroidism in children, in contrast to congenital hypothyroidism. Our objective was to assess the profile of JH in a referral clinic from eastern India. Materials and Methods: For this study, 100 patients with documented acquired hypothyroidism (subclinical and overt) (aged <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Short stature is a common feature of children with juvenile hypothyroidism once brain development is complete because thyroid hormones promote bone growth and skeletal development both directly and indirectly through their effects on the growth hormone. Juvenile hypothyroidism is caused by a lack of thyroid hormones as a result of the gland's destruction by autoimmune diseases [5][6]. When comparing the male and female genders, the latter had a significantly higher prevalence of short stature, which is consistent with the results of Gutch et al, where the female gender presented a double incidence of the condition [9].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Short stature is a common feature of children with juvenile hypothyroidism once brain development is complete because thyroid hormones promote bone growth and skeletal development both directly and indirectly through their effects on the growth hormone. Juvenile hypothyroidism is caused by a lack of thyroid hormones as a result of the gland's destruction by autoimmune diseases [5][6]. When comparing the male and female genders, the latter had a significantly higher prevalence of short stature, which is consistent with the results of Gutch et al, where the female gender presented a double incidence of the condition [9].…”
Section: Discussionsupporting
confidence: 86%
“…In underdeveloped nations with scarce access to healthcare, hypothyroidism is a key contributor to short stature. A study by Chowdhury et al revealed that 28% of female participants and 19% of male participants with short stature had hypothyroidism [6].…”
Section: Introductionmentioning
confidence: 99%